Seasonal, Interannual, and Spatial Variability in the Concentrations of Total Suspended Solids in a Degraded Coastal Wetland of Lake Ontario - Chow-Fraser P (Elsevier, 1999)
A 4-year (1993 through 1996) monitoring program examined the distribution of total suspended solids (TSS) in Cootes Paradise Marsh, a shallow (mean depth of 70 cm), degraded, drowned-rivermouth marsh of Lake Ontario. Monthly meteorological and hydrographical data from 1986 through 1996 revealed a hydrologically dynamic system that exhibited large seasonal and interannual variation with respect to precipitation amount, discharge volume, and water levels; the prevailing winds were shown to be oriented along the length of the marsh. Interannual variation in TSS concentrations was inversely related to mean seasonal water levels that fluctuated 45 cm over the 11 years. In a stepwise regression analysis, planktonic chlorophyll-a concentration only explained 2% of the variation in TSS, while inorganic and non-algal organic solids explained 70% and 18%, respectively. Mean seasonal water turbidity increased significantly with mean seasonal wind speed at 17 sampling stations during 1993 and 1994. Runoff from a summer rainstorm more than doubled water turbidities at the mouth of all three creeks over the first 36 hours. In enclosure experiments, water turbidity increased proportionately with biomass of benthivorous fish (especially common carp, Cyprinus carpio). When wind and carp disturbance were compared simultaneously in the field, wind speed accounted for 41% of the variation in turbidity while presence of carp explained an additional 21%. The overall temporal and spatial distribution of TSS in the marsh reflected changes in water level, wind activities, onset of rain events, and fish disturbance that acted in concert to keep Cootes Paradise Marsh extremely turbid throughout the summer.
Keywords: 41 Environmental Sciences; 31 Biological Sciences; 3103 Ecology; 4104 Environmental Management